2012
DOI: 10.3989/scimar.03506.02f
|View full text |Cite
|
Sign up to set email alerts
|

Life history traits of the invasive estuarine shrimp <i>Palaemon macrodactylus</i> (Caridea: Palaemonidae) in a marine environment (Mar del Plata, Argentina)

Abstract: SUMMARY: The invasive oriental shrimp Palaemon macrodactylus has been extensively recorded around the world, mainly in estuarine zones. In this study, the life history of this species was studied in Mar del Plata harbour (Argentina), a fully marine area where a stable and dense population has been established. Growth, sex proportion, morphological relationships, size at maturity and reproductive cycle were analysed between March 2007 and March 2009. A total of 9 and 7 modal classes (M1-M9) were detected in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…The potential explanations for the proportion of females higher than males include differential growth rates and mortality between sex, longevity, migration, and preference for different habitats (Berglund, 1981;Wenner, 1972), and this may also be a result of a sampling trawl due to the smaller male body size. A similar female-biased sex ratio was observed in palaemonid shrimp Palaemon macrodactylus Rathbun 1902, which reported deviation by predation by females on males observed in laboratory cultures (differential mortality) (Vázquez et al, 2012). In addition, Pianka (1983) proposed that in populations where the female copulates with more than one partner, the tendency of the sex ratio favors the increase in the number of females.…”
Section: F I G U R Ementioning
confidence: 62%
“…The potential explanations for the proportion of females higher than males include differential growth rates and mortality between sex, longevity, migration, and preference for different habitats (Berglund, 1981;Wenner, 1972), and this may also be a result of a sampling trawl due to the smaller male body size. A similar female-biased sex ratio was observed in palaemonid shrimp Palaemon macrodactylus Rathbun 1902, which reported deviation by predation by females on males observed in laboratory cultures (differential mortality) (Vázquez et al, 2012). In addition, Pianka (1983) proposed that in populations where the female copulates with more than one partner, the tendency of the sex ratio favors the increase in the number of females.…”
Section: F I G U R Ementioning
confidence: 62%
“…The difference between sexes in the use of refuge should be related with the sexual system of the species. As in other species of the genus, P. macrodactylus present an important sex dimorphism, with females reaching larger size than males (Berglund, 1981; Vázquez et al, 2012). This characteristic is associated with a “pure searching” mating strategy (Bauer, 2004).…”
Section: Discussionmentioning
confidence: 89%
“…Its dispersion due the human activity began in the 1950s and currently it has an almost worldwide distribution (Ashelby et al, 2013). Studies carried out on P. macrodactylus ' life history, reproduction and physiological capacity (Béguer et al, 2011; González‐Ortegón et al, 2006, 2013; Lejeusne et al, 2014; Omori & Chida, 1988a, 1988b; Vázquez et al, 2012; Vázquez, Ituarte et al, 2013, Vázquez, Bas et al, 2013) have shown that this species has the potential to live and reproduce successfully in a broad range of conditions, which is certainly important to their success as invader. However, we are far from understanding how these potentially important characteristics can come to operate from the introduction of a few individuals into a new environment.…”
Section: Introductionmentioning
confidence: 99%